IMPLEMENTATION OF COOPERATIVE LEARNING METHODS IN IMPROVING READING COMPREHENSION - HERLINA, ELIN (SIGEH ELT : Journal of Literature and Linguistics, 2022)
The purpose of this study was to determine the implementation of the Cooperative Learning Method in teaching reading comprehension, especially reading Factual Report texts to Class X Catering (JB) students at SMK Negeri 1 Ciamis, Ciamis District, Ciamis Regency, 2017/2018 Academic Year. This type of research is Classroom Action Research (CAR) and the design of this research refers to the Kemmis and Mc.Taggart model which consists of one action one cycle, which begins with planning, action, observation and reflection. This research was conducted in the odd semester of the 2017/2018 academic year, namely in October 2017. The subjects of this research were students of class X Catering Services (JB) SMK Negeri 1 Ciamis, totaling 31 people. The object of research is students' reading comprehension. Research data obtained through observation, interviews, documentation and reading comprehension tests. This study uses qualitative data analysis and quantitative data analysis. Quantitative methods were used to analyze the data on students' reading test results (pre-test and post-test) which could be used to analyze statistical data on descriptive text learning materials. Meanwhile, qualitative methods were used to analyze data from observations, student questionnaires, and interviews. The data obtained from quantitative and qualitative methods are then compared and matched to obtain the final conclusions from the research. This research consists of two cycles of 4 actions. The average pre-test showed an achievement of 60.48. The average post-test results in the first cycle of meeting 1 increased by 6.81 to 68.06. Cycle I meeting 2 increased from the previous cycle of 4.04 to 72.10. The second cycle of the first meeting increased by 1.44 to 74.2 and in the second cycle of the second meeting it increased by 0.98 to 83.9. The results showed that the Cooperative Learning Method could improve students' reading skills, especially factual report texts.